World environmental and water resources congress 2020, - Ahmad, Sajjad (Civil engineer) (American Society of Civil Engineers, 2020)
Selected papers from the World Environmental and Water Resources Congress 2020, held in Henderson, Nevada, May 17-21, 2020. Sponsored by the Environmental and Water Resources Institute of ASCE.This collection contains peer-reviewed papers on emerging and innovative technologies in water and environmental engineering.Topics include: cybersecurity and urban water infrastructure; smart technologies and water, wastewater, and stormwater; and international issues in water management.This proceedings will be of interest to practitioners and researchers in all areas of water resources engineering.
Keywords: Water resources management.; Water -- Distribution.; Climatic changes.; elektronické knihy; electronic books